A report on the practice-in-industry in fish processing technology - Antonio, Nida Hilario (Miagao, Iloilo College of Fisheries, 1978)
On the job training exposes the students to the real situation in industry. By actual involvement one can easily assess old or traditional methods used by the small factories compared to more sophisticated methods employed by big firms engaged in the same trade. One can never fully understand the problems encountered unless one works with them. Our industry today is looking forward to better quality finished products and newly formulated products especially canned ones. During the course of my practicum survey from different companies, important data are gathered from the workers especially the supervisors, thus enabling the author to evaluate these plants. The marked increase in the marketability of dried, frozen and canned products only shows that we are not far behind other countries in the exportation of processed fish products except for the smoked and fermented ones. This may be explained by great enthusiasm and desire of the different companies to compete with other exporting countries. This report covers training in various factories dealing with fish smoking, drying, freezing, fish sauce making and canning. This exposure has enabled one to gain practical experience and technical skills in the trade and put into practice what has been learned theoretically in the classroom through actual participation in all points in the production line. The practicum therefore, serves as an initial training ground for a graduate who intends to eventually get involved in fisheries not only as a theoretical discipline but as a potential income-generating commodity. The training was very profitable.
Report (Undergraduate, Fish Processing Technology) College of Fisheries, University of the Philippines, 1978.
Keywords: Fish -- processing